2022
DOI: 10.1186/s12877-022-03247-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between dependency on community resources and social support among elderly people living in rural areas in China: a cross-sectional study

Abstract: Background The prevalence of dependency personality disorder (DPD) is high among elderly people living in rural areas. This study aims to explore the association between dependency on community resources and social support among elderly individuals living in rural areas. Methods A cross-sectional study was conducted in 26 locations in China. A total of 1160 participants aged ≥ 60 years were selected using a complex multistage sampling design. All d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Social support is critical in enhancing family resilience and reducing caregiver burden 40 41. Interventions can help caregivers identify and access support networks, such as community resources and support groups 42. Expanding their support system allows caregivers to share their burdens and receive practical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is critical in enhancing family resilience and reducing caregiver burden 40 41. Interventions can help caregivers identify and access support networks, such as community resources and support groups 42. Expanding their support system allows caregivers to share their burdens and receive practical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, self-efficacy, as a positive psychological resource, can be used to assess the confidence of the elderly in their ability to obtain nutrition. Relevant studies have already confirmed that the self-efficacy of elderly people in rural China is relatively low and significantly different from that of elderly people in urban areas ( 48 ). So focusing on the self-efficacy of rural elderly populations will be an important measure to improve their nutritional literacy.…”
Section: Discussionmentioning
confidence: 99%
“…We also found social support was positively related to the level of PTG in Chinese adults with SLE ( r = 0.242, P < 0.01), although not significantly in the regression analysis. Social support is affected by culture, socioeconomic factors, and policies and impacts health through health behavioral pathways or psychological pathways [ 33 ]. It has been empirically demonstrated that social support plays an important role in the transition from trauma to growth, because it activates the cognitive processes that promote PTG [ 34 ].…”
Section: Discussionmentioning
confidence: 99%